2008
DOI: 10.1002/lapl.200810023
|View full text |Cite
|
Sign up to set email alerts
|

Short pulse duration of a 355-nm laser by extracavity sum-frequency mixing with a LiB3O5 (LBO) crystal

Abstract: A diode-pumped all-solid-state ultraviolet (UV) laser at 355 nm with pulse duration as short as 4.5 ns and peak power of 5.96 kW is proposed. The output UV light at 355 nm is obtained by extracavity sum-frequency mixing and has a power of 536 mW at the incident pump power of 15.65 W, corresponding to an optical-to-optical efficiency of 3.4%, the energy distribution of the UV light is near TEM00 and the power stability in an hour is better than ± 5.2%. Taking into account the thermal effects of the gain medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The laser performance of Pr 3+ ions has been reported [ 32 52]. In 2011, Xu et al, reported continu ous wave laser operation of Pr 3+ doped LiLuY 4 , LiYF 4 , and KYF single crystals in the red, orange, and 1 The article is published in the original. green spectral regions by using a new pumping scheme [53].…”
Section: Introductionmentioning
confidence: 96%
“…The laser performance of Pr 3+ ions has been reported [ 32 52]. In 2011, Xu et al, reported continu ous wave laser operation of Pr 3+ doped LiLuY 4 , LiYF 4 , and KYF single crystals in the red, orange, and 1 The article is published in the original. green spectral regions by using a new pumping scheme [53].…”
Section: Introductionmentioning
confidence: 96%
“…The extra-cavity harmonic generation using NLO conversion is an effective method to achieve high power, high pulse repetition frequency (PRF), and high beam quality UV laser [2,[7][8][9][10][11][12]. In [7] overall energy efficiencies on the order of 80% are predicted for the conversion of 1.0 μm laser radiation to the third harmonic.…”
Section: Introductionmentioning
confidence: 98%
“…LD pumped lasers with the Nd:YVO 4 crystal at 355 nm [2], 914 nm [3], and 1064 nm [14][15][16] are already available in commercial products and research field. However, scaling to higher power with good efficiency is still plagued by thermal aberrations and thermally induced fracture [17].…”
Section: Introductionmentioning
confidence: 99%